2018
DOI: 10.13057/biodiv/d190241
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, growth and genetic variations of sago palm (Metroxylon sagu) seedlings derived from seeds

Abstract: Riyanto R, Widodo I, Abbas B. 2018. Morphology, growth and genetic variations of sago palm (Metroxylon sagu) seedlings derived from seeds. Biodiversitas 19: 632-638. Propagations of Sago palm using seeds will result in large variations of seedlings due to segregation resulting in the genetic diversity. The objectives of this study are to observe the morphology, growth and genetic variations of sago palm seedlings derived from seeds resulted from natural pollination. Morphological diversities of sago palm seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Morphological characters of sago palm in Indonesia were reported high variation. Riyanto et al (2018) revealed that sago palm seedling showed in high variations based on morphology and genetic using RAPD markers. Abbas (2018) reported that sago palm high variation based on molecular markers, such as RAPD markers, Waxy gene markers, and rpl1671, NTCP21, and NTCP22 of cpDNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological characters of sago palm in Indonesia were reported high variation. Riyanto et al (2018) revealed that sago palm seedling showed in high variations based on morphology and genetic using RAPD markers. Abbas (2018) reported that sago palm high variation based on molecular markers, such as RAPD markers, Waxy gene markers, and rpl1671, NTCP21, and NTCP22 of cpDNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…The average leaf formation is around 2 leaves per month (Flach 1997). Leaf formation and growth patterns of sago palms is mainly influenced by genetic constitution (Riyanto et al 2018). Canopy of sago palm in the trunk stage consists of several leaves in the form of midribs and leaflets that grow to form a spiral pattern around the growth point located in the middle of the crown shoot.…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…Abbas et al (2017) stated that sago palm derived directly from the seeds varied genetically which may be caused by crosspollination and this may cause growth differences. Riyanto et al (2018) reported that growth of sago palm derived from seeds showed considerable variations. Sago palm grows faster and produces optimum starch when the environmental conditions are favorable, Several varieties of sago palm have high adaptability to the environment and will grow well in the waterlogged areas (Haryanto and Pangloli 1992).…”
mentioning
confidence: 99%
“…Abbas et al (2019) observed that no differentiation among sago palm accessions in the mitochondrial genome based on nad2 gene marker. However, the nuclear genome of sago palm from Papua islands highly varied identified by Random Amplified Polymorphic DNA (RAPD) marker (Riyanto et al 2018;Abbas 2018;Abbas et al 2009).…”
Section: Nucleotide Sequence Of Matk Genesmentioning
confidence: 99%